Image of Lord Ganesh over the main doorway of Koli homes - Mumbai Archive Project Team (Jio Institute, 2024)
The common religious decoration in Koli households is the placement of a small image of Lord Ganesha over the main doorway. It is believed that placing Lord Ganesha's presence at the doorway brings harmony and prosperity into the house.